Development of Flexible Learning Instruction Through Progressive, Personalized, Engaging and Diversified (FLIPPED) Video Media in Mathematics - Sagge, Roberto Jr.; Reyes, Lemar P. Delos (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Video media offers a novel way of learning. With its flexible learning features, such as options for review and accessibility anywhere, in-dividual learning needs are better met. This is advantageous when employed in a flipped learning setup for mathematics instruction, where learners need a significant amount of time to master a lesson. This developmental research design sought to develop flexible learning of instruction through progressive, personalized, engaging, and diversified (FLIPPED) video media as instructional materials for the least learned competencies in Grade 5 Mathematics, focusing on its application within a flipped classroom paradigm. The study em-ployed a competency-based assessment tool (CBAT) in Mathematics and a researcher-made evaluation form for the acceptability of the developed video media as its primary instrument. Findings highlight specific areas of challenges in Mathematics 5, such as formulating rules for sequence progression, visualizing fraction multiplication, estimating decimal products, identifying base, rate, and percentage, and finding the circumference of a circle. Utilizing the IPO model, the video media was meticulously developed to offer flexible learning that can improve mathematics achievement. The video media was rated as “highly acceptable” in terms of its flexible learning, progres-sive instruction, personalized instruction, learners’ engagement, and diversified instruction. The research findings conclude the efficacy of FLIPPED Video Media in addressing learning gaps and fostering a conducive learning environment that caters to diverse learning needs. The developed video media represents a paradigm shift in education, showcasing the transformative power of technology to enhance teaching and learning outcomes.